2018
DOI: 10.1111/jphp.12932
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-inflammatory activity of Tinospora cordifolia (Willd.) Miers chloroform extract – a preclinical study

Abstract: These findings encourage us strongly to focus on CETC to develop anti-inflammatory drugs with lower degree of inhibition to the constitutively expressing COX-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Tinospora cordifolia has an effect on the expression of cyclooxygenase-1, tumor necrosis factor-a, iNOS genes, cytokines (IL-6, IL-1b and PGE2) and NF-kB activation and has the potential to reduce the expression of the COX-2 enzyme and thereby reducing the expression of TNF-a, synthesis of IL-1B and IL-6 and other pro-inflammatory interleukins (Tiwari et al, 2018). The phytosterols such as stigmasterol and b-sitosterol found in T. cordifolia are found to be responsible for the inhibition of cyclooxygenase-2 synthesis and adhesion molecules in TNF-a stimulated by cells (Philip et al, 2018). Stigmasterol inhibits prostaglandin E2 and other matrix degradation mediators (Joshi & Kaur, 2016;Sharma et al, 2019;Singh & Chaudhuri, 2017;Tiwari et al, 2018;Upadhyay et al, 2010;Yanez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tinospora cordifolia has an effect on the expression of cyclooxygenase-1, tumor necrosis factor-a, iNOS genes, cytokines (IL-6, IL-1b and PGE2) and NF-kB activation and has the potential to reduce the expression of the COX-2 enzyme and thereby reducing the expression of TNF-a, synthesis of IL-1B and IL-6 and other pro-inflammatory interleukins (Tiwari et al, 2018). The phytosterols such as stigmasterol and b-sitosterol found in T. cordifolia are found to be responsible for the inhibition of cyclooxygenase-2 synthesis and adhesion molecules in TNF-a stimulated by cells (Philip et al, 2018). Stigmasterol inhibits prostaglandin E2 and other matrix degradation mediators (Joshi & Kaur, 2016;Sharma et al, 2019;Singh & Chaudhuri, 2017;Tiwari et al, 2018;Upadhyay et al, 2010;Yanez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The present study was aimed to elucidate the anti-cancer activity of chloroform (Chl-TCE) and hexane extracts (Hex-TCE) of T. cordifolia. Previous studies from our lab have reported the differentiation inducing potential and anti-cancer activity of 50% ethanolic extract of T. cordifolia (TCE) [9][10]. TCE was further fractionated by chloroform, hexane, ethyl acetate and butanol to explore the nature of expected active compounds and to reduce the effective dose on glioblastoma and neuroblastoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…TCE was further fractionated by chloroform, hexane, ethyl acetate and butanol to explore the nature of expected active compounds and to reduce the effective dose on glioblastoma and neuroblastoma cell lines. Chloroform and hexane fractions were found to possess anti-proliferative activity at very low doses (10 μg/ml of Chl-TCE and 15 μg/ml of Hex-TCE) as compared to effective doses of TCE (250 μg/ml and 350 μg/ml) for both the cell lines [9][10], whereas, ethylacetate and butanol fraction did not show anti-cancer activity ( Supplementary Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical analysis of Tinospora cordifolia (TC) revealed that it contains alkaloids, glycosides, sesquiterpenoids, lactones, and steroids 7 . So far studies have been carried out to evaluate the anti-inflammatory and immuno-modulatory properties of TC 8,9 . The effect of TC against AI has not been studied yet and therefore we evaluated the effectiveness of TC for the treatment of AI.…”
Section: Introductionmentioning
confidence: 99%